АНАЛІЗ ПРОЦЕСІВ У ПЕРЕТВОРЮВАЧІ КУКА З ІЗОЛЮЮЧОЮ СТРУКТУРОЮ З ВИКОРИСТАННЯМ МЕТОДА УСЕРЕДНЕННЯ - Руденко, Ю.В. (Інститут електродинаміки НАН України, Київ, 2022)
The processes in the Cook converter with an isoted transformer have been studied using the averaging method based on Lagrange's theorems in the mode of continuous currents and voltages in accumulating reactive elements. A mathematical model of the device based on relative variables is developed. Based on the developed model, analytical relations were obtained for the calculation of current ripple in the input and output chokes, as well as the voltage in the storage capacitors. Analytical dependences have been developed to determine the maximum values of currents and voltages in the switching elements of the converter in the entire switching range, which allows to reasonably select these elements of the device with acceptable parameters at the design stage. It is shown that neglecting the leakage inductance of the isolated transformer in the Cook converter when using expressions based on the developed mathematical model within certain limits of the transformation coefficient greatly simplifies their analytical appearance and use and does not lead to significant (more than 4-5%) deviations in calculation accuracy. References 10, figures 3.